2015
DOI: 10.1111/nyas.12640
|View full text |Cite|
|
Sign up to set email alerts
|

Multimodal neuroimaging evidence linking memory and attention systems during visual search cued by context

Abstract: Visual search can be facilitated by the learning of spatial configurations that predict the location of a target among distractors. Neuropsychological and functional magnetic resonance imaging (fMRI) evidence implicates the medial temporal lobe (MTL) memory system in this contextual cueing effect, and electroencephalography (EEG) studies have identified the involvement of visual cortical regions related to attention. This work investigated two questions: (1) how memory and attention systems are related in cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Generalized linear mixed models. Our response variable is binary-for a given observer and image a given grid cell was either fixated (1) or not (0). The observation matrix comprised 155,520 entries of zeros and ones (45 images × 72 subjects × 48 grid cells).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Generalized linear mixed models. Our response variable is binary-for a given observer and image a given grid cell was either fixated (1) or not (0). The observation matrix comprised 155,520 entries of zeros and ones (45 images × 72 subjects × 48 grid cells).…”
Section: Discussionmentioning
confidence: 99%
“…Research using simple displays has shown that attention and memory are coupled, as evidenced by interference between attention and features of items in visual working memory . In the context of natural scenes, however, it has remained controversial which features drive attention.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kasper, Grafton, Eckstein, and Giesbrecht combine EEG and fMRI to probe contextual cueing, in which learned stimulus configurations speed up target selection. They show that attentional processes interact with hippocampus‐related memory both for short‐ and long‐term implicit learning . Trapp and Bar review evidence that predictive top‐down activation biases competitive processing in favor of the correct stimulus interpretation, and suggest the orbitofrontal cortex as a neural substrate for such computation …”
mentioning
confidence: 99%